On video - Armes, Roy (Studies in communication., 1988)
Though video systems are now growing ever more accessible, and practical video work is undertaken at every level of education, this is the first book-length historical and theoretical study of the medium. On Video explores video on two levels: first, it examines the relationship between technology and society; and second, it probes the connection between production methods and the communication of meaning.